Performance and Meat Cholesterol Content of Broiler Chickens Fed Pluchea indica L. Leaf Meal Reared under Stress Condition - A Sudarman; . Sumiati; H Solikhah (Media Peternakan, 2011)
This experiment was conducted to study the effects of dietary addition Pluchea indica L. leaf meal on performances and meat cholesterol content of broiler. One hundred sixty two DOC CP707 strain were reared for four weeks in high stocking density of 15 birds/m2. The birds were fed experimental diets consisted of R1 (commercial feed + Vitastress), R2 (commercial feed + 2% P. indica leaf meal), R3 (commercial feed + 4% P. indica leaf meal), R4 (commercial feed + 6% P. indica leaf meal), and R5 (commercial feed + 8% P. indica leaf meal). The data obtained were analyzed using analysis of variance (ANOVA) and any significant differences were further tested using least significance difference (LSD) test. The treatment significantly increased (P < 0.05) final body weight, body weight gain, feed and water intake, and decreased (P < 0.05) feed conversion ratio.  It is concluded that P. indica leaf meal could be added into a diet at the level of 2%. P. indica leaf meal addition at the level of 2% into a diet is also able to decrease the cholesterol content of broiler meat up to 8%.